2005
DOI: 10.1042/bst0330384
|View full text |Cite
|
Sign up to set email alerts
|

The molecular biology of appressorium turgor generation by the rice blast fungus Magnaporthe grisea

Abstract: The rice blast fungus Magnaporthe grisea develops specialized infection structures known as appressoria, which develop enormous turgor pressure to bring about plant infection. Turgor is generated by accumulation of compatible solutes, including glycerol, which is synthesized in large quantities in the appressorium. Glycogen, trehalose and lipids represent the most abundant storage products in M. grisea conidia. Trehalose and glycogen are rapidly degraded during conidial germination and it is known that trehalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 28 publications
0
70
0
Order By: Relevance
“…36 However, in the study of Magnaporthe gasea, trehalose synthesis is required for virulence and it is possible that either trehalose accumulates as an accessory-compatible solute in appressoria or the sugar plays a role in the regulation of appressorium turgor generation. 37 Relative to mycelia, metabolites related to oxidative stress, such as carnitine, acetylcarnitine, oxylipins, ergothioneine, trehalose, mannitol, etc., are either not significantly changed or even reduced in conidia, which indicated that the oxidative stress is generated in the processes of transcription and translation. There is no significant oxidative stress reaction when the aaIT gene is quiescent in conidia.…”
Section: Resultsmentioning
confidence: 99%
“…36 However, in the study of Magnaporthe gasea, trehalose synthesis is required for virulence and it is possible that either trehalose accumulates as an accessory-compatible solute in appressoria or the sugar plays a role in the regulation of appressorium turgor generation. 37 Relative to mycelia, metabolites related to oxidative stress, such as carnitine, acetylcarnitine, oxylipins, ergothioneine, trehalose, mannitol, etc., are either not significantly changed or even reduced in conidia, which indicated that the oxidative stress is generated in the processes of transcription and translation. There is no significant oxidative stress reaction when the aaIT gene is quiescent in conidia.…”
Section: Resultsmentioning
confidence: 99%
“…One possible explanation is that the slender conidia of the Mgrho3 mutant may have less carbon storage than normal pyriform conidia. In M. grisea, carbon storage, such as in glycogen and lipid bodies, plays an important role in appressorium turgor generation (12,39). Therefore, it is likely that appressoria formed by the Mgrho3 mutants are defective in penetration because of the reduced turgor pressure.…”
Section: Discussionmentioning
confidence: 99%
“…While this reduction in epiphyllous growth was unexpected, it is not without explanation. The apparent inability of the DsakA mutant to penetrate the host cuticle is likely due to an inability to establish sufficient turgor pressure, or alternatively to produce degradative enzymes, for penetration (Wang et al, 2005;Noguchi et al, 2007). This would limit epiphyllous growth to those few hyphae that encounter and grow out of host stomatal openings, analogous to how some phytopathogenic fungi enter host tissues (Willmer and Fricker, 1996).…”
Section: Discussionmentioning
confidence: 99%